2022
DOI: 10.1039/d1ra07403b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical reduction of NO catalyzed by boron-doped C60 fullerene: a first-principles study

Abstract: Using DFT calculations, the potential of B-doped C60 fullerene is evaluated for electrochemical reduction of nitrogen monoxide. The B-doped C60 exhibits exceptional catalytic activity and high selectivity for reduction of nitrogen monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…According to Figures a and S4, all reaction steps to produce NH 3 on TM@MoS 2 (TM = Cr, Sc, Ti, Y, Zr, Nb, and Hf) are downhill. Therefore, their U L are 0 V, lower than those of most of the reported catalysts ,,, ,,, (Table S1). Over the TM@MoS 2 catalysts (TM = Ni, Mn, Fe, Co, and Rh; Figures b and S5), the only uphill step is the hydrogenation of *NO to *NHO, which naturally is their potential-determining step (PDS).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…According to Figures a and S4, all reaction steps to produce NH 3 on TM@MoS 2 (TM = Cr, Sc, Ti, Y, Zr, Nb, and Hf) are downhill. Therefore, their U L are 0 V, lower than those of most of the reported catalysts ,,, ,,, (Table S1). Over the TM@MoS 2 catalysts (TM = Ni, Mn, Fe, Co, and Rh; Figures b and S5), the only uphill step is the hydrogenation of *NO to *NHO, which naturally is their potential-determining step (PDS).…”
Section: Resultsmentioning
confidence: 77%
“…The final products of eNORR are NH 3 , hydroxylamine (NH 2 OH), and nitrous oxide (N 2 O) or N 2 . Among these products, in addition to NH 3 , NH 2 OH is also a very useful compound, involved in the production of caprolactam, a base chemical for the nylon industry. , Furthermore, NH 2 OH is a potential H 2 carrier in the renewable energy field . To date, pure transition metals (TMs) , , including noble metals, ,, alloys, , metal oxides, single-atom catalysts (SACs), and others have been tested for eNORR both experimentally and theoretically. Most of these studies focus on NH 3 , neglecting NH 2 OH.…”
Section: Introductionmentioning
confidence: 99%
“…A fullerene hybridization falls between graphite (sp 2 ) and diamond (sp 3 ) due to the curvature of the surface . In particular, heterofullerenes, which have one or more cage carbon atoms substituted by heteroatoms, have been found to be effective catalysts for electrochemical reactions such as oxygen reduction, , CO 2 RR, nitrogen monoxide electrochemical reaction, and CO oxidation. , The catalyst C 59 Si facilitates an oxygen reduction in acidic media through a four-electron pathway with a maximum electrode voltage of 0.8 V . Gao and Chen have discovered that C 59 B and C 59 N can act as efficient catalysts for CO oxidation reactions .…”
Section: Introductionmentioning
confidence: 99%
“…The C 59 B also shows excellent selectivity as a metal-free catalyst for NO electrochemical reduction with no limiting voltage. The reduction of NO results in the formation of NH 3 and N 2 O molecules at low and high coverages of NO, respectively . Furthermore, recent studies have shown that the surface curvature influences the electrocatalyst activity. In an earlier study conducted by Zhang et al, it has been reported that the COR activity is increased by curving a graphene material embedded with a porphyrin structure .…”
Section: Introductionmentioning
confidence: 99%